2014
DOI: 10.1016/j.asej.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotational speed modulation on heat transport in a fluid layer with temperature dependent viscosity and internal heat source

Abstract: In this paper, a theoretical investigation has been carried out to study the combined effect of rotation speed modulation and internal heating on thermal instability in a temperature dependent viscous horizontal fluid layer. Rayleigh-Be´nard momentum equation with Coriolis term has been considered to describe the convective flow. The system is rotating about it is own axis with non-uniform rotational speed. In particular, a time-periodic and sinusoidally varying rotational speed has been considered. A weak non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 50 publications
6
31
0
Order By: Relevance
“…It is observed that, in most of the cases there is significant effect of parameters on Nu and Sh at low values of time, but less effect at large time, since vibrations become smaller in magnitude, and disappear as Nu, Sh reach steady state value. The results of gravity modulation on the system preserve the results obtained by Bhadauria and Kiran [59] for rotational speed modulation.…”
Section: Resultssupporting
confidence: 81%
“…It is observed that, in most of the cases there is significant effect of parameters on Nu and Sh at low values of time, but less effect at large time, since vibrations become smaller in magnitude, and disappear as Nu, Sh reach steady state value. The results of gravity modulation on the system preserve the results obtained by Bhadauria and Kiran [59] for rotational speed modulation.…”
Section: Resultssupporting
confidence: 81%
“…while eliminating the pressure term, introducing the stream function  we obtain the following dimensionless governing system (Bhadauria et al [15,19]…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…They found that the modulated rotation speed has a stabilizing effect on the onset of convection for different values of modulation frequency and the other physical parameters involved. Bhadauria and Kiran [15] performed a weakly nonlinear thermal instability in a rotating fluid layer under rotation speed modulation using the Landau model. They found that instabilities are dominant for low frequencies and for small amplitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of amplitude and frequency of modulation is of similar effect under rotation speed modulation [53] which is originating idea from temperature modulation. The results in the case of lower boundary temperature modulation only were also obtained, but found to be qualitatively very similar to those obtain in OPM case, therefore not presented here.…”
Section: Nonlinear Throughflow Effects Under Modulationmentioning
confidence: 96%